If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(x+3)=14
We move all terms to the left:
-(x+3)-(14)=0
We get rid of parentheses
-x-3-14=0
We add all the numbers together, and all the variables
-1x-17=0
We move all terms containing x to the left, all other terms to the right
-x=17
x=17/-1
x=-17
| -4(3n+7)=12n | | 3(2x−4)+5=2x+5+6x3(2x-4)+5=2x+5+6x3(2x−4)+5=2x+5+6x | | 6y+5+71=180 | | 2m+3/11=1 | | (-2t-t^2)/(4-t)=t | | 200*x=7500 | | 0=779-16t^2 | | 2/7+1/5x-1/4=4/5x | | 10=n/3+13 | | 13M=32+5x | | 3y+0.25=3.25 | | 0=-4.45t^2-8t+200 | | 7/3+3m/4=49/12 | | y=(.25)-9+8 | | 1.48x+2.68(100-x)=184 | | 200•x=7500 | | n=11=1 | | (((7-3x)^(1/2))+(3/2)((7-3x)^(-1/2)))/(7-3x)=0 | | 4x-2=21-2x | | x*2-12x=-6 | | 12(3x+3)-7(2x-4)=2x-16 | | -8(3n+9)=14n | | y=(.25)2+8 | | k^2-8k-36=0 | | 7(x-10)=5(x+2 | | 6x-32+2x=-6 | | 7x-(x+4)=2x+8 | | (q/2)+(6/7)=(7q+12/14) | | (b^2-3b)^2-14(b^2-3b)+40=0 | | x-7=5/6(x+3) | | 2/3(6x+9)=-7x+3x | | 4x+7+7x-3=180 |